Minimal Blocking Concentrations of Bupivacaine and Procaine in an Exclusively Nociceptive System in Humans. Issue 4 (1st July 1999) - Holthusen, Holger; Lipfert, Peter; Klement, Wolfgang
Abstract : Background and Objectives: Prior to this investigation, there was no approach to compare both the potency of local anesthetics and their time course of action in a reproducible nociceptive system in humans. We tested whether the vascularly isolated vein segment is appropriate for such an approach. Methods: In six healthy men, a hand vein segment was vascularly isolated and intraluminally stimulated with electropulses of constant current intensity. The subjects rated pain between threshold and maximally tolerable pain on a visual analogue scale. For determining minimal blocking concentrations (a measure of potency), the vein segment was continuously perfused with Tyrode's solution with increasing concentrations of bupivacaine or procaine for at least 10 minutes each until pain was completely blocked. Subsequently, the respective local anesthetic was rinsed off with Tyrode's solution to determine the time course of recovery. Results: Both bupivacaine and procaine blocked pain in a concentration-related fashion, the minimal blocking concentrations being 1.6 (0.6-1.9; median and range) mmol/L for bupivacaine and 15.0 (7.5-22.5) mmol/L for procaine. Whereas the onset of block (time of 50% block) did not differ significantly between bupivacaine and procaine [43 s (range, 3-80) vs 53 s (range, 30-115)], local anesthesia lasted significantly longer after application of bupivacaine [278 s (range, 215-325)] than after procaine [183 s (range, 125-225)]. Conclusions: The vascularly isolated vein segment is well suited to compare in vivo the properties of local anesthetics with a minimally invasive approach at a reproducible nociceptive system in humans.